Trends in farmland tree stocks in the agroforestry landscape of northern Nigeria: Reconciling scientific and stakeholder perceptions. (February 2019) - Usman, Muhammad; Nichol, Janet
Abstract: A previous study indicated at least a doubling of farmland tree densities over five decades in the agroforestry landscape surrounding Kano, the largest city in savanna Africa. This increase, observed from field and remote sensing surveys, is surprising in the face of unprecedented population growth and availability of cheap manufactured substitutes for tree products. It also conflicts with the regional narrative for West Africa, derived mainly from observations and farm questionnaires, which suggests deforestation and reduced tree densities. This mismatch has previously resulted in failed initiatives to combat ecological crises, as extension services conceived at national and international level have met with little support and non-implementation at household level. To investigate the apparent mismatch we administered on-farm questionnaires in 55 villages. Open questions about trends in farmland tree stocks over several decades indicated declining tree stocks, but closed questions requiring tree enumeration and counting, indicated increase. Responses indicated difficulty in distinguishing between concepts of 'tree numbers' and 'tree species', as declining tree species diversity was reported by almost all responses, resulting from fuel wood demand and market trends towards a cash economy. This lack of distinction between tree species and tree numbers appears due to the traditional place occupied by farm trees in Hausa culture, where a tree species is inseparable from its use, combined with a deep sense of unease at the loss of cultural values. The study indicates that, despite more trees, the wide range of 'hungry foods' available from tree products, may no longer be available to alleviate future droughts, as during the 1970s and 80s, when productivity of agricultural and woody biomass plunged. However, initiatives to improve rural livelihoods may need to balance empirical observation against understanding of the complexity of stakeholder perceptions, as in this case overall tree stocks appear healthy, and the decline in species diversity is of greater concern. Highlights: Farm questionnaire data on farmland tree densities conflict with farmers' perceptions. Findings on farmland tree densities conflict with other reports of from the African Sahel. Loss of biodiversity due to population growth and urban demand for fuelwood. 'Hungry foods' and other tree products available in past droughts will no longer be available.